How to simply and efficiently screen microbial strains capable of anaerobic biosynthesis of biosurfactants: Method establishment, influencing factors and application example evaluation - Zhao, Feng; Wang, Yujing; Hu, Xin; Huang, Xinyu (Frontiers in Microbiology, 2022)
Microbial resources capable of anaerobic biosynthesis of biosurfactants are increasingly interested for their application in oxygen-deficient environments, such as in-situ microbial enhanced oil recovery and anaerobic bioremediation. How to simply and efficiently screen microbial strains capable of anaerobic biosynthesis of biosurfactants need be further studied in depth. In this study, an efficient and simple screening method was established based on the oil displacement characteristic of biosurfactants combined with the anaerobic culture technology using microplate assays. Strains whose anaerobic culture in microwells can form oil displacement circles with diameters larger than 10 mm were screened for scale-up culture in anaerobic tubes. The screened strains which can reduce the surface tension of anaerobic culture to lower than 45 mN/m were verified as positive strains. Using this screening method, eight positive strains and thirteen positive strains were screened from oil reservoir produced water and oily sludge, respectively. Through phylogenetic analysis, some screened strains were identified as Pseudomonas sp., Bacillus sp., and Enterobacter sp. This study also found that more microbial strains might be isolated after enrichment culture of environmental samples, whereas more microbial species would be isolated without enrichment. Suspension of environmental samples prepared with distilled water or normal saline had no significant effect. The established screening method is highly targeted and efficient for microbial strains capable of anaerobic biosynthesis of biosurfactants. The diameter of oil displacement circle is a reliable screening indicator. This study will contribute to explore more microbial resources which can anaerobically biosynthesize biosurfactants.